2022
DOI: 10.1021/acs.cgd.2c00581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Surfaces for Crystal Growth of a Photochromic Diarylethene by Sublimation

Abstract: The state of the substrate surface is one of the key factors in varying morphologies of crystals produced by the sublimation method of some organic compounds. In this work, we succeeded in separately preparing different morphologies of rodlike crystals of 1,2-bis­(2,5-dimethyl-3-thienyl)­perfluorocyclopentene (1a), which are classified into the hollow crystal and the feather-like crystal, by sublimation to glass substrates with the hydrophilic and hydrophobic surfaces, respectively. To clarify the crystal grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The crystal growth rate in the directions along the [100] direction is faster than that in the directions along the [111] direction as is evident from SEM images of the tip of each of the branched hollow crystals. In other words, the direction parallel to the straight line connecting the two vertexes with acute angles on the cross‐section of the hollow crystals is identified with the crystal growth direction of the feather‐like crystals, which undergoes the crystal growth process at the relative fast rate according to the crystal growth process of the feather‐like crystals observed by the digital microscope, according to our previous work [34] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The crystal growth rate in the directions along the [100] direction is faster than that in the directions along the [111] direction as is evident from SEM images of the tip of each of the branched hollow crystals. In other words, the direction parallel to the straight line connecting the two vertexes with acute angles on the cross‐section of the hollow crystals is identified with the crystal growth direction of the feather‐like crystals, which undergoes the crystal growth process at the relative fast rate according to the crystal growth process of the feather‐like crystals observed by the digital microscope, according to our previous work [34] …”
Section: Resultsmentioning
confidence: 99%
“…In other words, the direction parallel to the straight line connecting the two vertexes with acute angles on the cross-section of the hollow crystals is identified with the crystal growth direction of the feather-like crystals, which undergoes the crystal growth process at the relative fast rate according to the crystal growth process of the feather-like crystals observed by the digital microscope, according to our previous work. [34]…”
Section: Characterization Of Branched Shape Of Hollow Crystalmentioning
confidence: 99%
See 2 more Smart Citations
“…The self-assembly method offers an effective and fast way to make molecular crystals with different shapes and sizes from solutions. Moreover, it has been reported that complicated crystal topologies, such as unique tubular and hollow structures, could be obtained during crystal growth by regulating intermolecular interactions such as π-π interactions [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%